Charting the Course of Islamic Education Management Research: A Comprehensive Bibliometric Analysis for Future Inquiry - Ariona, Vanneza Diva; Inayati, Nurul Latifatul; Apriantoro, Muhamad Subhi; Ashfahany, Afief El; Tjandra, Eka Anugerah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to describe the development map and research direction of Islamic education management in Scopus database-indexed publications. This study used bibliometric analysis techniques to explore all publications indexed in the Scopus database on Islamic education management from 1983 to 2023. The data obtained were analyzed using Microsoft Excel and R/R-Studio. VOSviewer is used to visually analyze keyword occurrence and document citation stimulants. The author found 379 publications that fit the function, subject, and criteria set. The results of this study show that research with the theme of Islamic education management was mostly carried out in 2020. Indonesia is the country that contributes the most publications and is followed by Iran in second place. The highest affiliation is occupied by an Iranian university, Tehran University of Medical Sciences. The most relevant author is Majdzadeh, R. The source that has published the most writing on the theme of Islamic education management is the Eastern Mediterranean Health Journal. The limitation of this study is only taking metadata on publications indexed by Scopus. This study presents a brief overview of the literature accessible to researchers in Islamic education management and provides recommendations for future research.